2022
DOI: 10.9734/ijpss/2022/v34i242616
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effect of Phosphorous and Zinc on Yield Attributes, Yield and Quality Characteristics of Chickpea under the Central Plain Zone of Uttar Pradesh

Abstract: The present field experiments were conducted on studies effect of phosphorus and zinc on yield and quality parameters of chickpeas taken up at Student's Instructional Farm, at Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, (U.P.) India, during the rabi season 2021-22. The experiment consists of 16 treatment combinations in a factorial randomized block design with three replications consisting of a different combination of phosphorus and zinc. Chickpea variety RVG-203 was grown with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The maximum number of grains (57.67), length of ear (12.75 cm), fresh weight (156.24 g) and dry weight (25.25 g) of wheat were recorded in treatment T6 [125 % RDF + Azotobacter] followed by treatment T7 [100 % RDF + Azotobacter] with the value 54, 12.43 cm, 139.30 g and 22.52 g respectively, and the minimum number of grains (28.33), length of ear (7.25 cm), fresh weight (75.19 cm) and dry weight (12.15 g) of wheat was recorded in control. The results of the present investigation are also in agreement with the findings of Kumar et al, [14] Verma et al, [15] and Patyal et al, [16]…”
Section: Yield Componentssupporting
confidence: 93%
“…The maximum number of grains (57.67), length of ear (12.75 cm), fresh weight (156.24 g) and dry weight (25.25 g) of wheat were recorded in treatment T6 [125 % RDF + Azotobacter] followed by treatment T7 [100 % RDF + Azotobacter] with the value 54, 12.43 cm, 139.30 g and 22.52 g respectively, and the minimum number of grains (28.33), length of ear (7.25 cm), fresh weight (75.19 cm) and dry weight (12.15 g) of wheat was recorded in control. The results of the present investigation are also in agreement with the findings of Kumar et al, [14] Verma et al, [15] and Patyal et al, [16]…”
Section: Yield Componentssupporting
confidence: 93%
“…This might be on account of better translocation of nutrients specially P, resulting in to formation of bold seed by increasing the size and weight of seeds. Similar resulted were reported by Kumar et al [21]. The possible region of increase in these yield attributes could be that growth was much influenced by phosphorus application, which, later on, got converted in to reproductive phase.…”
Section: Yield Attributing Characterssupporting
confidence: 86%
“…The overall Fe yield increased, varying from 4 to 19% in parallel with the Fe fertilizer doses across environments (Table 9). Kumar et al [50] showed that the application of varying levels of Fe fertilizer up to 10 kg ha −1 significantly increased the Fe concentration in chickpea grain over a control. Similar findings were also reported by Sharma et al [51], who observed that the application of chelated Fe fertilizer improved the Fe content in seeds of pigeon pea.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the mechanism for increased Fe in seeds and the improved productivity of chickpea were due to an increased supply of Fe through an enhanced Fe status in the soil that resulted in a higher Fe uptake. Kumar et al [50] and Sahu et al [53] reported that the application of Fe fertilizer increased the grain yield of chickpea by 17.3%. Furthermore, the hundred-seed weight and seed yield were higher in resistant cultivars such as CDC Corinne, CDC Consul, CDC Leader and CDC Frontier compared to the susceptible cultivars CDC Alma and CDC Luna.…”
Section: Discussionmentioning
confidence: 99%